Ball milled glyco-graphene oxide conjugates markedly disrupted Pseudomonas aeruginosa biofilms. Issue 28 (7th July 2022) - Tricomi, Jacopo; Cacaci, Margherita; Biagiotti, Giacomo; Caselli, Lucrezia; Niccoli, Lorenzo; Torelli, Riccardo; Gabbani, Alessio; Di Vito, Maura; Pineider, Francesco; Severi, Mirko; Sanguinetti, Maurizio; Menna, Enzo; et al.
Abstract : Sugar headgroups have been grafted on the surface of graphene oxide (GO) by exploiting vibrational ball mills. The resulting glyco-GO conjugates significantly disrupt an already established P. aeruginosa biofilm. Abstract : The engineering of the surface of nanomaterials with bioactive molecules allows controlling their biological identity thus accessing functional materials with tuned physicochemical and biological profiles suited for specific applications. Then, the manufacturing process, by which the nanomaterial surface is grafted, has a significant impact on their development and innovation. In this regard, we report herein the grafting of sugar headgroups on a graphene oxide (GO) surface by exploiting a green manufacturing process that relies on the use of vibrational ball mills, a grinding apparatus in which the energy is transferred to the reacting species through collision with agate spheres inside a closed and vibrating vessel. The chemical composition and the morphology of the resulting glyco-graphene oxide conjugates (glyco-GO) are assessed by the combination of a series of complementary advanced techniques ( i.e. UV-vis and Raman spectroscopy, transmission electron microscopy, and Magic Angle Spinning (MAS) solid-state NMR (ssNMR) providing in-depth insights into the chemical reactivity of GO in a mechanochemical route. The conjugation of monosaccharide residues on the GO surface significantly improves the antimicrobial activity of pristine GO against P. aeruginosa . Indeed, glyco-GO conjugates, according to the monosaccharide derivatives installed into the GO surface, affect the ability of sessile cells to adhere to a polystyrene surface in a colony forming assay. Scanning electron microscopy images clearly show that glyco-GO conjugates significantly disrupt an already established P. aeruginosa biofilm.